2004
DOI: 10.1016/j.devcel.2004.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Role and Regulation of Starvation-Induced Autophagy in the Drosophila Fat Body

Abstract: In response to starvation, eukaryotic cells recover nutrients through autophagy, a lysosomal-mediated process of cytoplasmic degradation. Autophagy is known to be inhibited by TOR signaling, but the mechanisms of autophagy regulation and its role in TOR-mediated cell growth are unclear. Here, we show that signaling through TOR and its upstream regulators PI3K and Rheb is necessary and sufficient to suppress starvation-induced autophagy in the Drosophila fat body. In contrast, TOR's downstream effector S6K prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

52
1,044
6
13

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 900 publications
(1,115 citation statements)
references
References 47 publications
52
1,044
6
13
Order By: Relevance
“…16 UAS-Atg7 RNAi targets Atg7 by RNAi. 17,75 UAS-Flag-dronc encodes a Dronc protein with an N-terminal Flag-tag. 58 It was expressed using daughterlessGal4 (da-Gal4) in Mov34 mosaic background (Supplementary Figure S4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 UAS-Atg7 RNAi targets Atg7 by RNAi. 17,75 UAS-Flag-dronc encodes a Dronc protein with an N-terminal Flag-tag. 58 It was expressed using daughterlessGal4 (da-Gal4) in Mov34 mosaic background (Supplementary Figure S4).…”
Section: Methodsmentioning
confidence: 99%
“…14,15 Atg7 is an enzyme 1 (E1)-activating enzyme involved in both conjugation pathways 14 and essential for autophagy. 16 The incorporation of Atg8 fusion proteins (for example, with green fluorescent protein (GFP) and/or mCherry) into autophagosomes is often used as a marker for autophagosomes 17 and autophagic flux. 18 Although it was initially assumed that the UPS and autophagy are independent of each other, recent evidence has suggested that there is crosstalk and feedback between the two 1,[19][20][21][22][23][24][25][26][27] (reviewed by Park and Cuervo, 3 Wojcik 28 and Lamark and Johansen 29 ).…”
mentioning
confidence: 99%
“…9 Premature death from the third larval to pupal stages was reported in D. melanogaster mutants. 10,49 Finally, dauer formation is abnormal in Caenorhabditis elegans autophagy mutants. 24 Although these phenotypes seem to be diverse, all of them are closely related to nutrient status and starvation.…”
Section: Developmentmentioning
confidence: 99%
“…10 In addition, we recently revealed that autophagy is also quite important to help mammals survive a unique period of starvation, the birthing process. 11 It is known that neonates face severe starvation at birth due to sudden termination of the placental nutrient supply.…”
Section: Introductionmentioning
confidence: 99%
“…4 These studies have demonstrated that while autophagy is often induced as part of an adaptive response, induction of autophagy may also lead to cell death. During Drosophila larval development, for example, starvation-induced autophagy occurs in the larval fat body and is required for maintaining circulating nutrient levels and survival of the larvae under unfavorable nutritional conditions; 5 by contrast, programmed autophagy results in cell death and is the primary means of removing certain larval organs during metamorphosis. 6 On a cellular level, autophagy is observed prior to apoptosis in growth factor-deprived neuronal cultures.…”
mentioning
confidence: 99%